Prescribing Pattern of Cardiovascular Drugs - A Prospective Observational Study - Thomas, Blessy Rachel; TJ, Catherin; Sabu, Neetha; ES, Lekshmi; Baby, Neenu; K, Menaka; T, Sivakumar (Indian Journal of Pharmacy Practice)
Cardiovascular diseases are the most endangering illness prevalent in India. Compared to the past, cardiovascular diseases are showing an escalated trend due to the changes in lifestyle and social habits. Drugs are the bedrock of treatment and prevention of cardiovascular diseases. Factors like low utilization rates of evidence based therapies, high drug cost and long duration of therapy hinder the rational usage of cardiovascular drugs. The aim of the study is to assess the prescribing pattern of drugs in cardiovascular disease. A prospective observational study conducted in a tertiary care hospital for a period of 3 months from April 2017 to June 2017. In the study, 123 patients were enrolled and assessed with their demographic data, medical history and drugs prescribed. In this study, among 123 cases of cardiovascular diseases assessed, the incidence of cardiovascular diseases was common in males (84%) and more prevalent in age group 51- 60 years. While assessing the prescribing pattern of cardiovascular drugs, antiplatelets (90.24%), anticoagulants (55.28%), thrombolytics (4.87%), antianginals (68.29%), antihyperlipidemics (81.3%), antihypertensives (87.80%) and ionotropes (22.76%) were the drugs prescribed. Increasing age, random changes in lifestyle, lack of physical activities, increased stress, work load, smoking like habits have been providing a path to more morbidity and mortality. Drug-drug interaction is a trouble maker in management of cardiovascular diseases as it requires multiple therapies. Effective strategies, regular monitoring has to be implemented to improve the patient compliance and achieve a better outcome.
Keywords: Cardiovascular diseases; Prescribing pattern; Cardiovascular drugs; Rational drug use; Compliance